2019
DOI: 10.1021/jacs.9b05603
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Gd3N@C80 Prato Bis-Adducts: Crystal Structure, Thermal Isomerization, and Computational Study

Abstract: The structures of two bis-ethylpyrrolidinoadducts of Gd3N@I h -C80, obtained by regioselective 1,3-dipolar cycloadditions, were elucidated by single crystal X-ray, visible-near infrared (vis-NIR) spectra, studies on their thermal isomerization, and theoretical calculations. The structure of the minor-bis-adduct reveals a C 2-symmetric carbon cage with [6,6]­[6,6]-addition sites and with an endohedral Gd3N cluster that is completely flattened. This is the first example of a crystal structure of Gd3N@I h -C80 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…[1][2][3][4] Exohedral functionalization of EMFs has shown its effectiveness to broaden their applications by generation a variety of useful derivatives. During the last decades, many synthetic methods have been applied to modify EMFs, among which cycloadditions, such as the BingelHirsch reaction, 5,6 [2+2] benzyne addition, 7, 8 1,3dipolar reaction, [9][10][11][12] DielsAlder reaction, 13 carbene addition 14 and so on, 5,15,16 have been widely utilized. Results show that the chemical properties of EMFs are much different from those of empty fullerenes, resulting in a fact that some chemical reactions which are effective to C 60 do not work on EMFs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Exohedral functionalization of EMFs has shown its effectiveness to broaden their applications by generation a variety of useful derivatives. During the last decades, many synthetic methods have been applied to modify EMFs, among which cycloadditions, such as the BingelHirsch reaction, 5,6 [2+2] benzyne addition, 7, 8 1,3dipolar reaction, [9][10][11][12] DielsAlder reaction, 13 carbene addition 14 and so on, 5,15,16 have been widely utilized. Results show that the chemical properties of EMFs are much different from those of empty fullerenes, resulting in a fact that some chemical reactions which are effective to C 60 do not work on EMFs.…”
Section: Introductionmentioning
confidence: 99%
“…[20,46] This is a feature typically seen in the synthetically challenging multiadducts of NCFs which, understandably, has ordered clusters fixed by multiple organic groups. [47,48] The crystal of 4 was further studied at different temperatures. First, at 120 K, the final difference density map reveals ordered sites for all cluster atoms (Figure 3 a, top).…”
Section: Methodsmentioning
confidence: 99%
“…33 In functionalized NCFs, fully ordered clusters were mostly achieved via direct and strong interactions between the functional group and the cage (e.g., multiadditions or formal charge on the ligand and cage, etc.). 16b 21c 24 34 Our work demonstrated that weak intermolecular interactions between the organic ligands and the NCF cage can also restrict the cluster motion in the solid state of synthetically straightforward monoadducts, which provides a new direction of materials design for magnetic and quantum applications.…”
Section: Isocyanide-induced Fullerene/emf Reactions With Substituted ...mentioning
confidence: 99%